The Influence of Teacher Skills Using the Whatsapp Application, powerpoint and Assessment Techniques on the Professionalism of Primary School Teachers Inpress Loka Bantaeng District - Nurlaidah Nurlaidah; Agustan Agustan; Idawati Idawati (Universitas Muhammadiyah Enrekang, 2023)
The implementation of learning is still less varied, the learning process has a tendency towards certain methods (conventional), and does not pay attention to the level of students' understanding of the information conveyed. Students are less active in the learning process, students listen and write more, causing the lesson content to be rote so that students do not understand the actual concept. This study examines the effect of teacher skills using the Whatsapp application, Powerpoint and assessment techniques on the professionalism of teachers at SD Inpres Loka Uluere District, Bantaeng Regency. This type of research used quantitative research with descriptive research type. The sample technique used is saturated sampling of 48 homeroom teachers with research instrument measurements namely; likerts scale. The data analysis technique used is descriptive statistical analysis techniques and multiple regression analysis techniques with the help of the SPSS version 26 software application. Based on the results of research and analysis of teacher skills data using the Whatsapp application, Powerpoint and assessment techniques on teacher professionalism at SD Inpres Loka Uluere District, Bantaeng Regency, it was known that the calculated F value = 28,476 with a significant level of 0.000, less than <0.05, the variable (X ) has a strong effect on variable (Y) thus it can be seen that Ha is accepted and H0 is rejected because of the Sig value. smaller than 0.05. So it can be concluded that there is an influence of Teacher Skills Using the Whatsapp Application, Powerpoint and Assessment Techniques on Teacher Professionalism at SD Inpres Loka Uluere District, Bantaeng Regency.